Eco-services, the Natural Capital Way to Sustainable forest Management and Development - Walia, J. S. (Indian Forester, 2008)
Sustainability means survival, livelihoods and environmental services. Himachal’s economic valuation of natural capital and eco-services, such as direct non-consumptive benefits and goods has shown the importance of looking holistically at eco-systems and eco-services. Ecotourism provides a sustainable solution towards handling mountain community upliftment through a participatory mode between the different stakeholders involved. For sustainable development to work with natural ecosystems and their goods and services, a combination of regulatory constraints and market mechanisms are needed.